Réponses

2014-09-10T09:36:03+02:00
A = 2/14 - 3/7
A = 2/14 - 3 x 2 / 7 x 2
A = 2/14 - 6/14
A = - 4/14
A = 2 x 2 / 2 x 7
A = 2/7

B = 7/5 + 3/4
B = 7 x 4 / 5 x 4 + 3 x 5 / 4 x 5
B = 28/20 + 15/20
B = 43/20

C = 1/20 + 3/28
C = 1 x 28/ 20 x 28 + 3 x 20 / 28 x 20
C = 28/ 560 + 60/560
C = 88/560
C = 8 x 11 / 8 x 70
C = 11/70

D = 12/5 : 7/5
D = 12/5 x 5/7
D = 60/35
D = 5 x 12 / 5 x 7
D = 12/7

E = (8/6 - 2/3) x (4 - 2)
E = (8/6 - 2 x 2 / 3 x 2) x 2
E = (8/6 - 4/6) x 2
E = 4/6 x 2
E = 8/6
E = 2 x 4/ 2 x 3
E = 4/3